Implementation of Deep Breathing Relaxation for Chest Pain Management in Heart Disease Patients - Nurhusna, Nurhusna; Putri Irwanti Sari; Yulia Indah Permata Sari (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2024)
Pain is the most complex human experience and is a phenomenon that is influenced by interactions between emotions, behavior, cognitive and physiological sensory factors. Pain as a subjective sensory and unpleasant emotional experience is related to actual or potential tissue damage or is felt in events described by the term damage. The cause of pain is not only life-threatening diseases such as cancer, but also injuries, surgery, burns, infections and the effects of violence. A person also experiences pain from many of the procedures and investigations used by doctors and nurses to investigate and treat disease. Pain can be managed by pain management by taking deep breaths. Deep breathing relaxation techniques can reduce pain by relaxing muscle tension that supports pain. The relaxation technique consists of slow, rhythmic, abdominal breathing. The patient can close his eyes and breathe slowly and comfortably. The aim of this service is to provide knowledge and skills in managing pain for heart disease sufferers with clinical symptoms of pain immediately after the pain appears, which can be done by the patient or with the guidance of the family. The method used was counseling for patients and families with heart disease who were undergoing treatment at the Heart Care Unit at Raden Mattaher Hospital, Jambi, totaling 20 people. The results of the service activities showed that there were changes in respondents' knowledge regarding non-pharmacological pain management, and increased ability to perform deep breathing techniques for pain management.